Factors Influencing the Participation of Small-Scale Fishermen in Marine Protected Areas in East Java - Efani, Anthon; Manzilati, Asfi; Riza, Muhammad Faisal (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
Marine Protected Areas (MPA) were created to address overfishing, which can harm fishing communities and reduce the number of fish. This affects how much food is available and how happy people feel, especially for people who work as small-scale fishermen. They depend on catching fish to meet their needs. This study aimed to find out what factors affect fishermen's choice to participate in MPAs. It was done in Malang and Probolinggo Regencies in East Java, with 200 fishermen involved in the research. This research gathers information by asking people questions through a survey. The survey has a set of questions that are planned. The economist studies the probit model to determine what factors affect fishermen's choice to join MPAs. The findings indicated that factors like family members, marital status, number of fishing gear, market access, and savings did not have a noteworthy impact on the involvement of small-scale fishermen in MPAs. But, things like how old they are, how much education they have, whether they belong to a fishermen's group, if they work outside of fishing, and if they are part of a cooperative all greatly impact whether small fishermen participate in MPAs.